An interrelation of physical and technical readiness as a basis in sport result achievement of 400 m hurdlers - Oleg Grebeniuk (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to establish the relationship of physical and technical preparedness to achieve sports results of 400 m hurdlers at the stage of preliminary base preparation. Material & Methods: study involved the first grade athletes in the amount of 18 people. Methods of research: pedagogical observation, pedagogical experiment, pedagogical testing of physical and technical readiness, telepodometry, methods of mathematical statistics. Results: it found that the major indicators of special physical readiness in the step of preliminary base preparation are: run at 100 m. result which was 96.4% from the model; run at 200 m - 96,0% from the model; run at 400 m - 98,7% from the model; hopping run 100 m - 93,4% and jumps 20 m on one leg - 91,1% % from the model. Conclusion: study of individual elements technique allows us to characterize not only the technique of movements, but also the level of physical qualities.